EVALUATION OF DIFFERENT TRANSPORT AND ENRICHMENT MEDIA FOR THE ISOLATION OF HELICOBACTER PYLORI - Rizvi, Farhat; Hannan, Abdul (Journal of Ayub Medical College Abbottabad, 2000)
Background: Helicobacter pylori are traditionally difficult to grow on culture media. The present study aims to determine the optimal transport and culture media for growing the microorganisms. Methods: One hundred antral biopsies were obtained in duplicate from patients complaining of upper GIT symptoms. Growth was obtained from 44% biopsies transported in Semi Solid Motility Medium (SSMM) and 42% from thioglycolate broth. This difference was not statistically significant (p = 0.l). Brain Heart Infusion Agar (BH1) plus 7% Horse Red Blood Cells (HRBC) plus SR69 (antibiotic supplement) was found to be the best of three culture media for isolation of H. pylori, with a growth rate of 45% (p=<0.001). Results: This study shows that H. pylori is a common cause of gastro-duodenal disease in Pakistan. Proper transport and selection of culture media is required for optimal isolation from gastric biopsies